Detection of rickettsia rickettsii brumpt (RICKETTSIALES: RICKETTSIACEAE) in the brown dog tick rhipicephalus sanguineus latreille (IXODIDA: IXODIDAE) in the comarca lagunera, a reemergent spotted fever zone in Mexico - Castillo-Martínez, Antonio; Cueto-Medina, Saraí M.; Valdés-Perezgasga, María Teresa; Sánchez-Ramos, Francisco J.; López-Hernández, Javier; Hernández-Rodríguez, Sergio; Ortega-Morales, Aldo I. (Instituto de Ecología, A.C., 2017)
Rocky Mountain Spotted fever is a reemergent disease in the Comarca Lagunera, since numerous human cases have been reported in the last few years. In order to detect the presence of Rickettsia rickettsii Brumpt in dog´s brown ticks, single collections of ticks were conducted in seven rural areas and a periurban area in the Comarca Lagunera of Coahuila and Durango from June 2015 through february 2016. Direct collection of 840 engorged female ticks on 168 home dogs was carried out (5 ticks per dog), which were contained in two  ml vials. Ticks were identified as Rhipicephalus sanguineus Latreille in the Parasitology Laboratory of the Universidad Autonoma Agraria Antonio Narro Unidad Laguna. For the molecular analysis three ticks per sample ticks were randomly selected, forming 195 pools. Each tick was subjected to extraction of internal organs and stomachal content. CTAB technique was used on each pool in order to obtain DNA, gltA gene was amplified using PCR assays with thermocyclator and a generic primer (Forward: RpCS.844p, Reverse: RpCS. 1258n).Eight pools resulted positive to Rickettsia rickettsii with a frecuency of 6.9% (2/29) in the colony Leticia Herrera (Gomez Palacio, Durango), one (1/26= 3.85%) for Parras (Coahuila) and five pools for the municipality of Matamoros (Coahuila) in Granada (2/28=7.1%), Alamito (1/23=4.35%), Consuelo (1/32=3.13%) and Vizcaya (1/19=5.25%). By means of  sequenciation 100% identification for Rickettsia rickettsii Brazilian strain 647 (KJ588069.1) and 99% for InDRE stractions (KU587806.1 and KT881097.1) were obtained.